Acute appendicitis in children - review focused on diagnostics and treatment - Wardal, Wiktoria; Brzozowska , Monika; Furlepa , Natalia; Rzenno , Robert; Wojciechowska , Karolina; Matuszewska , Marcelina; Wicha , Katarzyna; Sidz , Natalia; Tomaszewska , Magdalena; Jedlikowska , Wiktoria (Quality in Sport, 2025)
Introduction and Objective Appendicitis is one of the most common surgical conditions in both children and adults. There are numerous diagnostic tools available, as well as a variety of treatment options, including both pharmacological and surgical methods. This summary focuses on the current knowledge regarding the disease, its diagnosis and treatment. Review Methods A literature review was conducted using the PubMed database to gather information on appendicitis. The main search term used was "appendicitis," with the review specifically concentrating on the diagnosis and treatment of the condition. Description of the State of Knowledge Diagnosing appendicitis involves taking a medical history, performing a physical examination, conducting laboratory tests, and using imaging, which also help assess the severity of the condition. Treatment options range from antibiotic therapy to open surgery and laparoscopic appendectomy. Conclusions The analysis of the review suggests that both diagnosis and treatment depend on various factors, with the patient's clinical presentation and the surgeon's experience being among the most important. Treatment approaches are continually evolving, such as with the development of different laparoscopic techniques, including one-incision laparoscopic appendectomy in addition to the conventional three-incision method. However, more traditional treatments, like antibiotic therapy and open appendectomy, remain in use. Key words: appendicitis; children; diagnostics; treatment; appendectomy